Bright aspects of defects and dark traits of dopants in the photoluminescence of Er2X2O7:Eu3+ (X = Ti and Zr) pyrochlore: an insight using EXAFS, positron annihilation and DFT. Issue 9 (12th April 2021) - Gupta, Santosh K.; Sudarshan, K.; Jena, Paramananda; Ghosh, P. S.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.
Abstract : This work investigated the origin of blue PL in undoped and absence of Eu 3+ red PL in the doped Er2 X2 O7 (X = Ti and Zr) pyrochlore using photon, positron and X-ray as spectroscopic probe and further complimenting with DFT. Abstract : Understanding the intricacies and fundamental processes of materials involved in dopant- and defect-based luminescence is of paramount importance for scientists and engineers working towards the design of solid-state lighting, optoelectronics, scintillators, etc. The lack of such fundamental information has restricted the design of new oxide-based materials for light-emitting devices and phosphor-converted materials. Here, we have designed Er2 Ti2 O7 (ETO), Er2 Zr2 O7 (EZO), Eu 3+ -doped ETO (EETO), and Eu 3+ -doped EZO (EEZO) via high-energy ball milling. Structural analysis using X-ray diffraction (XRD) and Raman spectroscopy suggested the stabilization of the ordered pyrochlore structure for ETO and EETO, whereas EZO and EEZO are stabilized in the defect fluorite structure. The ETO and EZO samples exhibited bright blue emission under ultraviolet irradiation. X-ray absorption near edge structure (XANES) analysis completely rules out contributions from Ti 3+ or Zr 3+ to the host emission via confirming that they exist as tetravalent ions. Extended X-ray absorption fine structure (EXAFS) analysis confirms the presence of a high density of oxygen vacancies (OVs) near the Ti and Zr sites, respectively, in ETO and EZO. The DFT-calculated charge transition levels qualitatively explain the origin of the blue emission of ETO and EZO with the dominant involvement of ionized oxygen vacancies. Positron annihilation lifetime spectroscopy (PALS) suggested that few changes in the defect density or type occurred upon europium doping in EETO. The defect concentration and type change significantly in EEZO with respect to EZO, which is of significant importance due to the possible agglomeration of vacancies into large-size defect clusters in EEZO. Surprisingly, in both hosts, red/orange narrow emission from europium (585–750 nm, 5 D0 → 7 F J ) was completely absent. Density of state (DOS) calculations suggested that a possible reason for this is that the Eu f-states are dominantly distributed around the bottom edge of the valence band (VB), far from the Fermi energy, electronic band gap, and top edge of the VB actively participating in the electronic transitions. Similarly, the Eu f-states are distributed around the top edge of the conduction band, far from the electronic band-gap region. We believe this work will be quite helpful for selecting suitable hosts and dopants, band gap engineering, and defect tuning in the pursuit of achieving efficient host-to-dopant energy transfer in Eu 3+ -doped pyrochlore materials.